2018
DOI: 10.1002/hlca.201800066
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Nucleobase Analogues with Extended Pi Surfaces Stabilize DNA Duplexes Containing O6‐Alkylguanine Adducts

Abstract: Chemical alkylation of DNA produces potentially toxic and mutagenic damage such as O6‐alkylguanine (O6‐alkylG) adducts. Non‐natural nucleoside analogues that pair with DNA adducts provide a potential basis for studying damaged DNA. Herein, we evaluated the base pairing properties of elongated nucleoside analogues containing napthalene‐derived tricyclic nucleobases as DNA adduct‐pairing nucleoside analogues in DNA hybridization probes. DNA duplex melting studies revealed that the elongated nucleoside analogs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…The predicted structure with the lowest potential energy was O 6 -MeG­( syn ):Per­( syn ), which precludes hydrogen bonding (Figure B,C). This observation is consistent with a previous study indicating that π-stacking interactions of these nucleobase analogues promote duplex stability . However, the next-lowest-energy structure was with Per in the anti conformation (Figure S11), thus restoring hydrogen bonding.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predicted structure with the lowest potential energy was O 6 -MeG­( syn ):Per­( syn ), which precludes hydrogen bonding (Figure B,C). This observation is consistent with a previous study indicating that π-stacking interactions of these nucleobase analogues promote duplex stability . However, the next-lowest-energy structure was with Per in the anti conformation (Figure S11), thus restoring hydrogen bonding.…”
Section: Results and Discussionsupporting
confidence: 92%
“…This observation is consistent with a previous study indicating that π-stacking interactions of these nucleobase analogues promote duplex stability. 76 However, the nextlowest-energy structure was with Per in the anti conformation (Figure S11), thus restoring hydrogen bonding. Thus, whether Per is in the syn or anti conformation, for both lowest-energy conformations, O 6 -MeG is predicted to be in a syn conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DNA adduct-directed artificial nucleotides have been developed as a basis for interrogating damaged DNA in duplex hybridization or polymerase-mediated synthesis contexts . We have reported a variety of nucleoside analogues that stabilize damaged DNA vs undamaged DNA. The heterocyclic imidic nucleoside analogue derived from benzimidazolinone (Benzi) and a derivative with an extended ρ-surface termed ExBenzi (Figure B) consist of a conjugated π-system, a hydrogen bond accepting carbonyl group, and an imino-based hydrogen bond donor. When placed opposite O 6 -alkylG adducts, the resulting duplexes are stabilized. When ExBenzi was included in short oligonucleotides attached to gold nanoparticles, the presence of O 6 -alkylG adducts in target DNA strands disrupted nanoparticle aggregation and induced a color change, indicating the presence of the adduct .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a variety of nucleoside analogues that stabilize damaged DNA vs undamaged DNA. The heterocyclic imidic nucleoside analogue derived from benzimidazolinone (Benzi) and a derivative with an extended ρ-surface termed ExBenzi (Figure B) consist of a conjugated π-system, a hydrogen bond accepting carbonyl group, and an imino-based hydrogen bond donor. When placed opposite O 6 -alkylG adducts, the resulting duplexes are stabilized. When ExBenzi was included in short oligonucleotides attached to gold nanoparticles, the presence of O 6 -alkylG adducts in target DNA strands disrupted nanoparticle aggregation and induced a color change, indicating the presence of the adduct . These hybridization probes provide an excellent quantitative read-out, but do not involve DNA amplification and have so far been used to detect down to 138 fmol of modified DNA in 6 pmol of total DNA.…”
Section: Introductionmentioning
confidence: 99%
“…24 Dangling-end T m measurements, where the synthetic nucleoside is unpaired and overlaps with the adjacent terminal base pair, confirmed that ExBIM and ExBenzi stabilized the duplex more than Benzi and BIM and supported the hypothesis for enhanced surface area overlap with the neighboring base on the opposing strand. 24 Further, while Benzi, BIM, ExBenzi, and ExBIM are fluorescent (quantum yields Φ f = 0.35, 0.82, 0.69, and 0.44, respectively), the fluorescence of ExBIM was the most sensitive to the altered chemical environment imposed by the presence of the adduct. Thus, ExBIM showed the highest adduct selectivity.…”
Section: ■ Introductionmentioning
confidence: 99%